A gestão democrática da educação: expectativas da escola sobre a participação da família - Inforsato, Edson do Carmo [UNESP]; Inforsato, Fátima Aparecida Ferreira; Rodrigues, Inês Marini; Fontes, Valéria Longobardo (My University, 2011)
The objective of this study was to verify the importance of family involvement as an element of democratic school management challenging legislation, intellectual discourse and the perspective of school staff. For this purpose, we analyzed the information obtained by means of instrument PDESchool applied in the public schools of a medium-sized city in the state of São Paulo. We found that the school teams identify school / family interaction as an important factor in the work to be developed, although families show little involvement in the management of school units.

El objetivo de este estudio fue verificar la importancia de la participación de la familia como un elemento de la gestión democrática de las escuelas frente a la legislación, los discursos escolares y la visión del equipo escolar. Para ello, hemos elaborado un análisis de la información obtenida por el instrumento de la PDE-Escuela, aplicado en la red de un municipio de tamaño medio de São Paulo. Se encontró que los equipos escolares vinculan la interacción de la escuela y la familia como un factor importante para el trabajo que se desarrolla, aunque las familias tienen poca participación en la gestión de la unidad escolar.

O objetivo deste trabalho foi o de verificar a importância da participação da família na gestão democrática das escolas, confrontando a legislação, os discursos intelectuais e a visão das equipes escolares e analisando as informações levantadas pelo instrumento PDE-Escola, aplicado na rede de um município de porte médio do Estado de São Paulo. Verificou-se que as equipes das escolas apontam a interação entre escola e família como fator importante no trabalho a ser desenvolvido, embora as famílias tenham pouco envolvimento na gestão da unidade escolar.
Democratic educational management: school expectations on family participation
Gestión democrática de la educación: expectativas de la escuela sobre la participación de la familia
Keywords: Public policy; Education; Social control; Social participation and family; Políticas públicas; La educación; Control social; Participación social y familia; Política pública; Educação; Controle social; Participação social e família